1987
DOI: 10.1002/polb.1987.090251007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of initial morphology and molecular weight on the deformability of poly(ethylene terephthalate)

Abstract: Solution‐grown crystal (SGC) mats and solution‐cast (SC) films of poly(ethylene terephthalate) (PET) were drawn by solid‐state coextrusion followed by tensile drawing of the coextrudates. Drawabilities and properties of the drawn films, such as mechanical and thermal properties, were investigated as functions of molecular weight, initial morphology, and drawing conditions. The initial morphology and molecular weight have a marked effect on the drawability and tensile properties of the resultant drawn films. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It is well-known that the strain at break of cross-linked polymer networks in the rubbery state is directly connected to the entanglement density through the relation λ max ∝ N e 1/2 , where N e is the chain length between entanglements (including cross-links) given in number of random links. This was shown to fairly apply to the elongation at break of various semicrystalline polymer networks including UHMWPE. In the present study, it is likely that for sintering at 150 °C, healing by interface re-entanglement would not be completed at 150 °C. As a consequence the crystalline network could hide any difference until fracture, but near the fracture the material is expected to be more sensitive to the possible weakness of the entanglement network.…”
Section: Results and Data Analysismentioning
confidence: 60%
“…It is well-known that the strain at break of cross-linked polymer networks in the rubbery state is directly connected to the entanglement density through the relation λ max ∝ N e 1/2 , where N e is the chain length between entanglements (including cross-links) given in number of random links. This was shown to fairly apply to the elongation at break of various semicrystalline polymer networks including UHMWPE. In the present study, it is likely that for sintering at 150 °C, healing by interface re-entanglement would not be completed at 150 °C. As a consequence the crystalline network could hide any difference until fracture, but near the fracture the material is expected to be more sensitive to the possible weakness of the entanglement network.…”
Section: Results and Data Analysismentioning
confidence: 60%
“… where ϕ holds for the polymer concentration in the solution prior to crystallization. Similar behavior has been reported for poly(propylene),65 poly(ethylene terephthalate),66 poly(4‐methylpent‐1‐ene),67 and nylon 6 68. On the one hand, such experiments give evidence that only the entangled network resists drawing when the molecular mobility in the crystalline phase is high enough.…”
Section: Polymer Extensibility In the Solid Statementioning
confidence: 82%
“…Modeling of necking dynamics was attempted by the introduction of the strain‐hardening and strain‐rate dependences in the material constitutive law 58, 74. Neck profiles of HDPE and iPP were fairly well predicted by finite element calculations, including the temperature sensitivity 66, 78–81. No structural factors have yet been proposed by the authors to account for the observed effects, as well as no physical explanation for the natural draw ratio.…”
Section: Theoretical Approaches To the Natural Draw Ratiomentioning
confidence: 99%
“…We report the effects of initial morphology on the deformation behavior and the structure of the resultant drawn films. 13,14 For the drawn samples from initially amorphous state, the crystallinity increases with increasing the DR due to the strain-induced crystallization. However, the crystallinity from initially highly crystalline material decreases with DR. During the drawing, the crystals existed in the predrawn material are destroyed, and simultaneously strain-induced crystallization happens but the degree of crystallization is not high enough to reach the original crystallinity.…”
Section: Drawing Behaviormentioning
confidence: 98%